Technospheric Mining of Rare Earth Elements from Bauxite Residue (Red Mud): Process Optimization, Kinetic Investigation, and Microwave Pretreatment. Issue 1 (December 2017) - Reid, Sable; Tam, Jason; Yang, Mingfan; Azimi, Gisele
Abstract Some rare earth elements (REEs) are classified under critical materials, i.e., essential in use and subject to supply risk, due to their increasing demand, monopolistic supply, and environmentally unsustainable and expensive mining practices. To tackle the REE supply challenge, new initiatives have been started focusing on their extraction from alternative secondary resources. This study puts the emphasis on technospheric mining of REEs from bauxite residue (red mud) produced by the aluminum industry. Characterization results showed the bauxite residue sample contains about 0.03 wt% REEs. Systematic leaching experiments showed that concentrated HNO3 is the most effective lixiviant. However, because of the process complexities, H2 SO4 was selected as the lixiviant. To further enhance the leaching efficiency, a novel process based on microwave pretreatment was employed. Results indicated that microwave pretreatment creates cracks and pores in the particles, enabling the lixiviant to diffuse further into the particles, bringing more REEs into solution, yielding of 64.2% and 78.7% for Sc and Nd, respectively, which are higher than the maximum obtained when HNO3 was used. This novel process of "H2 SO4 leaching-coupled with-microwave pretreatment" proves to be a promising technique that can help realize the technological potential of REE recovery from secondary resources, particularly bauxite residue.